(untitled) (Nigerian Journal of Physiological Sciences, 2020)
The interest in the role of vanadium compounds in living organisms has grown tremendously especially since the report of its glycemic normalization activity in the 1980s. There has been reports of both its toxic as well as positive effects, thus there is a paucity of information on the essentiality of this element in biological systems. In this study, the effect of different doses of sodium metavanadate on the haematological and biochemical variables of male Wistar rats was investigated. Twenty male Wistar rats were divided into four groups of five each and were given tap water containing various concentrations of sodium metavanadate (0ppm- group 1, 50ppm- group 2, 100ppm- group 3, or 200ppm- group 4) for 10weeks. Weekly body changes were noted and blood was collected at the end of 10 weeks by retro orbital puncture for haematological and serum biochemical variables. Histological sections were also performed on liver and kidney tissues. There was a significant increase in body weight in the 50ppm group compared with control. Sodium metavanadate at 200ppm caused a significant decrease in packed cell volume (PCV), red blood cell count (RBC), white blood cell count (WBC) and Lymphocytes with significant increases in neutrophils and neutrophil-lymphocyte ratio when compared with control values. There was also a significant decrease in ALP, ALT and a significant increase in urea concentration in the 200ppm group when compared with control values. All doses of sodium metavanadate significantly reduced blood glucose level. Sections of liver and kidney revealed severed damage at 200ppm compared with control. The results from this study showed that vanadium affects both haematological and biochemical parameters and could be toxic at higher concentrations, while at low concentration could be beneficial as seen with the enhanced body weight